Ethnobotanical uses in the Ancona district (Marche region, Central Italy) - Lara Lucchetti; Silvia Zitti; Fabio Taffetani (Journal of Ethnobiology and Ethnomedicine, 2019)
Abstract Background The study is a survey of the traditional uses of plants in the Ancona district, in the Marche region, Central Italy. Methods The information derives from ethnobotanical investigations conducted with an open questionnaire among the rural population in three areas of the Ancona district that are representative of the socio-economic and environmental assets of the entire district: the Mount Conero area on the Adriatic coast; the municipality of Osimo, as an inland hilly area; and the ‘Gola della Rossa–Frasassi’ area, in the Apennines. Results A total of 120 informants cited 195 species. The ethnobotanical data concern medicinal (122 species), food (119), veterinary (53), superstitious/religious (61), cosmetic (30), domestic (27), dyeing (17), recreational (17), repellent (15), craft (10), and miscellaneous (29) uses, along with inclusion in local sayings and proverbs (25). The species with the greatest number of categories of use here was Sambucus nigra L. Among the other species with the greatest numbers of categories of use, there were Matricharia chamomilla L., Salvia officinalis L., Urtica dioica L., Papaver roheas L., and Rosa canina L. For each use, comparisons with national and regional literature were made. Conclusions Some uses are commonly known across the three areas; others are sectoral and are new for the Marche region. The survey increases our present-day knowledge of the traditional local uses of plants in the Marche region, in terms of medicinal and food uses, and of ethnobotanical aspects as a whole, which will allow many of these uses to be preserved in the future.